The Influence Of Financial Literacy On Household Financial Management Among Fishermen In Watolo Village, Central Buton Regency - Xena Agnisya Putri; Anwar; Tenri Sayu Puspitaningsi Dipoatmojo (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to examine the extent to which financial literacy influences the financial management ability of fishing households in Watolo Village, Central Buton Regency. Fishermen are a community group that depends heavily on weather conditions and market dynamics, making their income unstable between fishing and lean seasons. In such conditions, the ability to manage income becomes an essential factor in maintaining family economic resilience. Financial literacy, which includes knowledge, attitudes, and skills in understanding and managing personal finances, is believed to play a significant role in improving the welfare of fishermen. This research employs an associative quantitative approach involving 60 respondents who are active heads of fishing households in Watolo Village. Data were collected through a Likert scale questionnaire and analyzed using simple linear regression. The results indicate that financial literacy has a positive and significant effect on household financial management, with a regression coefficient of 0.430, R value of 0.542, R² of 0.294, and a significance level of 0.000 (<0.05). These findings confirm that the higher the level of financial literacy, the better the fishermen’s ability to manage income, record financial flows, and plan long-term savings. The implication of this study is the need for community-based financial education programs and coastal economic empowerment policies tailored to the income characteristics of fishermen to strengthen their resilience against seasonal risks. Keywords: financial literacy; financial management; fishermen household; Central Buton